PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN RELIGIUSITAS CULTURE DI SMK MUHAMMADIYAH MARAWOLA - Muh. Dihyah. L (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2020)
The results of this study indicate that Islamic religious education teachers are already professional in carrying out theirduties and responsibilities. Most of the students who attend SMK Muhammadiya Marawola, seem to have goodReligiosity. There are several ways of Islamic religious education teachers at Muhammadiyah Marawola VocationalSchool in improving the religiosity of Muslim students, namely by planning, implementing, and evaluating.The implication of this study is that Islamic religious education teachers work together with the guardians of students tomonitor the attitudes and behavior of students outside the school environment. Thus the religiosity activities that havebeen applied have the benefit of changing the attitudes and behavior of students in the environment where students live,especially for both parents.